Nondestructive Detection of Vegetable Moisture Content and Storage Time Using Microwave Free-Space Reflection Method - LI Chenxiao, REN Yuan, ZHAO Chenyu, HE Xian, YU Xiaoting, XU Yanlei (Shipin Kexue, 2023)
In this study, a radar traveling-standing wave detection device for the rapid and nondestructive detection of the moisture content and storage time of vegetables was designed based on the microwave free-space reflection method. Spatial traveling-standing waves generated by microwave free-space reflection and superposition were explored and the changes in standing wave ratio and the coordinate of antinode as a function of the moisture content and storage time of vegetables were investigated. The results showed that the proposed models had good prediction accuracy. The goodness of fit (R2) of the moisture content prediction models for lettuce and leaf lettuce were 0.979 and 0.959, and the standard errors of prediction (SEP) were 0.310% and 0.641%, respectively. The R2 values of the storage time prediction models for lettuce and leaf lettuce were 0.992 and 0.951, and the SEP values were 0.173 and 0.285 days, respectively. This study provides a new method for nondestructive testing of vegetable quality.